2023
DOI: 10.47853/fas.2023.e14
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric relations and diet compositions of Nile tilapia Oreochromis niloticus (Linn. 1758) in Lake Tana Gorgora gulf, Ethiopia

Abstract: Oreochromis niloticus is the most ecologically and economically important fish in tropical and sub-tropical aquatic systems. Recently, due to sever anthropogenic stressors, hydrological variations and infestations of invasive alien species in Ethiopian water bodies, fish community structure and ecosystem of Lake Tana is changing alarmingly. So far, there is paucity of information on the morphometric relations and diet composition of O. niloticus in Lake Tana, gulf of Gorgora. A total of 309 fish samples were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(82 reference statements)
0
0
0
Order By: Relevance
“…The stomach content analysis of O. niloticus suggests that it is primarily an herbivorous fish that feeds on plant-based food items such as green algae, plant tissues, and plant seeds, as well as detritus. Herbivorous feeding habits of O. niloticus have also been reported in Ethiopian water bodies such as Lake Chamo (Teferi et al, 2000), Koka Reservoir (Engdaw et al, 2013) and Lake Hayq (Assefa and Getahun, 2015). However, this result was in disagreement with Oso et al (2006), who suggested that O. niloticus has omnivorous feeding habits.…”
Section: Es Qfs Hfs Tqfs Fsmentioning
confidence: 81%
See 1 more Smart Citation
“…The stomach content analysis of O. niloticus suggests that it is primarily an herbivorous fish that feeds on plant-based food items such as green algae, plant tissues, and plant seeds, as well as detritus. Herbivorous feeding habits of O. niloticus have also been reported in Ethiopian water bodies such as Lake Chamo (Teferi et al, 2000), Koka Reservoir (Engdaw et al, 2013) and Lake Hayq (Assefa and Getahun, 2015). However, this result was in disagreement with Oso et al (2006), who suggested that O. niloticus has omnivorous feeding habits.…”
Section: Es Qfs Hfs Tqfs Fsmentioning
confidence: 81%
“…This high stomach vacuity index may be attributed the post-harvest digestion or the method of catching of the specimens. Engdaw et al (2013) also reported an empty stomach for O. niloticus, caught with gill nets in Ero and Koka reservoir. The reason for this may be due to the fact that the food items in their stomach may have been regurgitated or digested as the fish struggled for escape in gill nets during the catches.…”
Section: Es Qfs Hfs Tqfs Fsmentioning
confidence: 91%